N, 2, 3, 4‐Tetrasubstituted Pyrrolidines through Tandem Lithium Amide Conjugate Addition/Radical Cyclization/Oxygenation Reactions. Issue 22 (14th July 2016) - Kafka, František; Pohl, Radek; Císařová, Ivana; Mackman, Richard; Bahador, Gina; Jahn, Ullrich
Abstract : Enantioselective syntheses of densely functionalized pyrrolidines deriving their chirality from ( R )‐1‐(phenyl)ethylamine are reported. Allylic amines and β‐substituted‐α, β‐unsaturated esters are used as the building blocks in this one‐pot reaction. Single electron transfer (SET) oxidation served to merge the reactivities of anionic enolate and radical intermediates. Ferrocenium hexafluorophosphate, which is easy to prepare, store and handle, was applied as SET oxidant and persistent free radical TEMPO served as the oxygenating agent introducing a protected hydroxy function, which proved to be beneficial for further derivatization. Exclusive 2, 3‐ trans and up to 6:1 3, 4‐ cis/trans diastereoselectivities were achieved in the targeted tetrasubstituted pyrrolidines. Abstract : Readily available chiral allylic amines and α, β‐unsaturated esters are used to synthesize densely substituted pyrrolidines with exclusive 2, 3‐ trans and up to 6:1 3, 4‐ cis/trans configuration in a tandem polar lithium amide conjugate addition/radical cyclization/oxygenation sequence.